Corneal welding via infrared lasers: in vitro & in vivo studies - Rasier, Rıfat. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2017., 2017)
Infrared lasers can be used to weld soft tissues. Water molecules and also protein molecules such as collagen absorb the infrared energy and a temperature gradient can be created at the application site. Objective of this PhD thesis is to investigate the potential of infrared lasers for welding tissue to contact lens and also for cornea welding in order to seal corneal cuts done during cataract surgery. One of the new application in the field is our study about amniotic membrane welded to contact lens by 1470-nm diode laser: a novel method for sutureless amniotic membrane transplantation. This study showed a new method for laser welding of a tissue to contact lens for ophthalmologic application. Corneal welding is rather a new application area in laser medicine, and few studies reported successful welding dose for different infrared wavelengths. Full thickness, oneplane 3.2 mm long clear corneal cuts were done using a pre-calibrated knife. Laser power and irradiation duration were the parameters used and histological indicators of photothermal effect were observed. In the field of corneal laser welding we made experiments which 809-nm, 908-nm, 1070-nm and 1980-nm laser used to weld clear corneal incisions. According to these in-vitro studies and their histologic results, another experiment was planned to compare 1070-nm and 1890-nm wavelengths which we found the best results in previous studies. In this thesis, in vitrocornea laser weldingexperiments were performed also with 1470-nm diode laser which have high water absorption. According to preliminary results; in-vivo rabbit study was planned with the best two energy parameters options of 1470-nm diod laser which we had with the in-vitro study. Full thickness, one-plane 3.2 mm long clear corneal cuts were done using a pre-calibrated knife under anesthesia. After irradiation, rabbit cornea’s were observed in postoperative first day, first week, second week and forth week. In this thesis it is possible to find a wide range of studies and their results about laser welding. In the light of the findings of these studiesit may be predicted that laser welding applications will have much more place in all biomedical applications.
Keywords: Cornea -- Laser.; Cornea -- Surgery.